If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3n + -8 = 4n Reorder the terms: -8 + 3n = 4n Solving -8 + 3n = 4n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-4n' to each side of the equation. -8 + 3n + -4n = 4n + -4n Combine like terms: 3n + -4n = -1n -8 + -1n = 4n + -4n Combine like terms: 4n + -4n = 0 -8 + -1n = 0 Add '8' to each side of the equation. -8 + 8 + -1n = 0 + 8 Combine like terms: -8 + 8 = 0 0 + -1n = 0 + 8 -1n = 0 + 8 Combine like terms: 0 + 8 = 8 -1n = 8 Divide each side by '-1'. n = -8 Simplifying n = -8
| 19=-9x+1 | | k^2+18=9k | | 27-2p=-9+7p | | Xy+7x=56 | | 9x-12=-60 | | 1-2=43 | | 16r^2s^2= | | 1/2x=7.5 | | -8w-8=-7w | | 3y+4x+18=44 | | 3y=5y+9 | | 3x+2=3x+50 | | x-18/24=4/1.4 | | nm=10 | | 27/32•4/9 | | 4-n/6=3 | | 1/2x-4=14 | | 9r-2s-3rt+7s= | | (2x^2y)(-3x^2y^3)=0 | | (2x^2y)(-3x^2y^3)= | | 2q=-10+4q | | 7b+3a+5-7-2b= | | w=1/2l | | -7-7v=3v+84 | | 120x^2+5x=0 | | 5-4+7x+1=9x+9 | | -41/x−17/x=-39 | | [(4-8)x2-10]/2 | | -66-5n=6+7n | | .4(3x-20)+.6=x+3.8 | | 5-4+7x+1=0x+1 | | 22x+23= |